Manipulation of oil synthesis in Nannochloropsis strain NIES-2145 with a phosphorus starvation–inducible promoter from Chlamydomonas reinhardtii - Iwai, Masako; Hori, Koichi; Sasaki-Sekimoto, Yuko; Shimojima, Mie; Ohta, Hiroyuki (Frontiers in Microbiology, 2015)
Microalgae accumulate triacylglycerols (TAGs) under conditions of nutrient stress. Phosphorus (P) starvation induces the accumulation of TAGs, and the cells under P starvation maintain growth through photosynthesis. We recently reported that P starvation–dependent overexpression of type-2 diacylglycerol acyl-CoA acyltransferase (CrDGTT4) from Chlamydomonas reinhardtii using a sulfoquinovosyldiacylglycerol synthase 2 (SQD2) promoter, which has increased activity during P starvation, enhances TAG accumulation in C. reinhardtii cells. As a result, the content of C18:1 fatty acid, a preferred substrate of CrDGTT4, is increased in TAGs. Here we isolated genes encoding SQD2 from strain NIES-2145 of the eustigmatophyte Nannochloropsis and showed that their expression, like that in C. reinhardtii, was up-regulated during P starvation. To enhance oil accumulation under P starvation, we transformed pCrSQD2-CrDGTT4 into Nannochloropsis strain NIES-2145. The transformants had a fatty acid composition that was more similar to that of C. reinhardtii, which resulted in enhanced TAG accumulation and higher 18:1(9) content. The results indicated that the P starvation–inducible promoter of C. reinhardtii was able to drive expression of the CrDGTT4 gene in Nannochloropsis strain NIES-2145 under P starvation. We conclude that the heterologous CrSQD2 promoter is effective in manipulating TAG synthesis in Nannochloropsis during P starvation.